Associação Brasileira de Psicologia do Esporte (ABRAPESP): história e contribuições para área - Ramos, Debora Adriana (2020)
The area of Sport Psychology is increasingly in evidence in Brazil, having its peak in 2016 when more than 33 Sport Psychologists, hired by the Brazilian Olympic Committee, worked directly with athletes in the Rio de Janeiro Olympics. At that moment, it was evident to the population, the important presence of the Sports Psychologist on the committee of any sports delegation. When the spotlight was directed to professionals in Sport Psychology, the importance of knowing the Brazilian Association of Sport Psychology (ABRAPESP) is emphasized. Thus, the present study has as main objective to tell a little about the history and contributions of this Association. For that, a beam of light falls on seven of the eight presidents who underwent the management of that association, where, through their narratives and other analyzed documents, it was possible to illuminate the origin and current functioning of ABRAPESP. The interviews prioritized knowing who they were, how they came to Sport Psychology, each person's professional performance, the reasons for running for the presidency of the institution, their goals in management, the positive and negative points perceived when they presided over an association. Semi-structured interviews were conducted, with an average duration of 50 minutes, through Google Meet, which were duly recorded and transcribed. To complement the information, the collection of data related to the activities carried out by the Association since its foundation, with an emphasis on biannual congresses and its Magazine, was done through documents from ABRAPESP (documentary and virtual research). In the results, we highlight that the history of the Association is permeated with challenges and achievements, as it did and is part of important moments of Psychology and Sport in Brazil and worldwide. The desire to establish an Association that would give a voice to sports psychologists was born within the Regional Council of São Paulo (CRP / SP) and in partnership with the Sedes Sapiencie Institute, first to set up a training course in the area since 2000. Regarding the trajectory of the presidents' lives, it is possible to perceive a connection with the sport, going through their degrees through other areas of Psychology, but knowing that they wanted to be in that area. The emergence of ABRAPESP in this path is evidenced in each speech, in these the Sports Psychology professional highlights his space and discloses his performance in the most different fields, illustrating that in this course people who have been fighting for the dissemination and legitimation of the area for more than 20 years (1980 - 2000). Among the goals of the Association throughout all administrations is the incentive to improve the qualification and services of sports psychologists, ensuring high ethical and professional standards; encouragement to carry out scientific studies in the areas of Sport Psychology, as well as the dissemination of practical and research activities by these professionals, always with the aim of stimulating and supporting the creation of study groups to aggregate interested or already working psychologists in the area. In the report of their presidents, the greatest motivation was to make congresses a means of bringing together professionals in the field to exchange knowledge and experiences through conferences, lectures, li courses with national and international professionals with expertise in the area. On average, congresses gather around 200 to 300 people in person, reaching 1200 internet users in events broadcast on Facebook and Instagram. Another means of scientific dissemination of ABRAPESP is through the Revista Brasileira de Psicologia do Esporte (RBPE), the only specific national magazine on the area, in activity since 2007, with 127 articles published until today, including in its contents an interface between the different sciences of the sport, beyond Psychology. Another result provided by the union of professionals through ABRAPESP was the creation of two working groups, one with the Federal Council of Psychology and another at the National Association of Research and Graduate Studies in Psychology (ANPEPP), since 2016. In view of the material analyzed, it was possible to conclude the relevance of this institution, from its creation and maintenance to the present day, bringing together professionals and adding ethical and scientific values to the professional performance in Brazilian Sport Psychology.